Visual quality assessment of historical street scenes: a case study of the first “real” street established in Baghdad - Mundher, Riyadh; Al-Sharaa, Ammar; Al-Helli, Marwah; Gao, Hangyu; Abu Bakar, Shamsul (MDPI AG, 2022)
Historical street scenes materialize essential cultural and artistic values for the cities in which they are located and their citizens. However, the visual quality of historical scenes is susceptible to a number of causes that could result in their deterioration. These causes can be environmental or man-made, with either generating elements that may influence the perceived visual quality of historical scenes. Therefore, this research is to assess the visual quality of historical street scenes and identify the elements that can potentially impact them. The study adopted a photo survey approach employing a Likert Scale as the main method to assess visual quality. In addition, a heatmap analysis technique was utilized to identify the elements that impact the visual quality of historical street scenes. The results indicate respondents’ high levels of dissatisfaction with the visual quality of Baghdad’s historical street scenes. The results also showed that modern facade materials, security concrete walls, and degraded buildings’ facades are elements that had a negative impact to the overall scenic quality. On the other hand, historical religious buildings, urban greenery, and unique historical buildings are elements that have a positive impact on the visual quality of historical street scenes. This research represents an approach for evaluating the visual impact and visual quality of historical street scenes, providing a quantitative tool for future initiatives focusing on the visual quality of historical legacy scenes. This research is a starting point for both researchers in urban conservation and architectural history, and municipal offices of improving the visual quality of historic streets scenes.